2013
DOI: 10.1080/13562517.2012.719157
|View full text |Cite
|
Sign up to set email alerts
|

‘Getting it Write’ in social work: exploring the value of writing in academia to writing for professional practice

Abstract: Writing plays a central role in social work practice and in the qualifying programmes studied by student social workers. The research on which this paper is based explores the value of writing undertaken in higher education to writing for professional practice in social work. Drawing on data sources from a 'text oriented ethnography', this paper explores the reflections of five recently qualified social workers making the transition from academic to professional practice. The significance of this study is heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 24 publications
1
32
0
2
Order By: Relevance
“…Key findings from work placement writing, echoed in more recent small studies (e.g. Leon and Pepe 2010;Lillis and Rai 2012;Rai and Lillis 2012), point to the limited opportunities for "newcomers" to learn, or critically evaluate, the required writing genres (e.g. Paré and Le Maistre 2006) and to the limited attention paid to such genres in social work education (e.g.…”
Section: Existing Research On Writing In Social Work Practicementioning
confidence: 94%
See 1 more Smart Citation
“…Key findings from work placement writing, echoed in more recent small studies (e.g. Leon and Pepe 2010;Lillis and Rai 2012;Rai and Lillis 2012), point to the limited opportunities for "newcomers" to learn, or critically evaluate, the required writing genres (e.g. Paré and Le Maistre 2006) and to the limited attention paid to such genres in social work education (e.g.…”
Section: Existing Research On Writing In Social Work Practicementioning
confidence: 94%
“…Paré and Le Maistre 2006) and to the limited attention paid to such genres in social work education (e.g. Lillis and Rai 2012;Rai and Lillis 2012). Other researchers such as Hall et al (2010) and White et al (2010), exploring the organizational systems governing social work practice in Children's Services, have raised questions about the ways in which predesigned ICT (information and communications technology) systems orient social workers towards description and away from narrative, making it difficult for even the most informed readers to grasp a holistic understanding of any single person's case.…”
Section: Existing Research On Writing In Social Work Practicementioning
confidence: 99%
“…This traditional dichotomy between academic and professional contexts and texts is further enhanced in a globalised world, which has increasingly become the professional arena for social workers. It is, therefore, not only the differences between academic and professional texts that are to be negotiated, but also the different cultural, academic, and textual traditions in the world that must be considered (Rai and Lillis 2013). Thus, the key task for social workers is to find strategies to meet the challenges of a global society.…”
Section: Social Work and Academic Writingmentioning
confidence: 99%
“…Meanwhile, a number of multi-disciplinary studies [4,10,14,21] have shown that professional writing plays an important role in various countries, domains and specific subjects. Thus, how to achieve enhancement in writing ability becomes a concerned topic.…”
mentioning
confidence: 99%